2004
DOI: 10.1111/j.1600-0765.2004.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and C‐reactive protein‐associated cardiovascular risk

Abstract: This study indicated that periodontitis may add to the inflammatory burden of the individual and may result in increased levels of cardiovascular risk based on serum CRP concentrations. These observations will need to be confirmed in a definitive trial. Given the high prevalence of periodontitis in the population, these data would caution physicians to be aware of the possible oral source of an increased inflammatory burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
2
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(198 citation statements)
references
References 30 publications
(32 reference statements)
8
173
2
15
Order By: Relevance
“…If these clinical diagnostic tests could be applied to the screening of periodontal disease, the problems described above could be overcome (4)(5)(6)(7)(8)(9). Some reported studies have demonstrated a correlation between blood test parameters and periodontal status.…”
Section: Introductionmentioning
confidence: 99%
“…If these clinical diagnostic tests could be applied to the screening of periodontal disease, the problems described above could be overcome (4)(5)(6)(7)(8)(9). Some reported studies have demonstrated a correlation between blood test parameters and periodontal status.…”
Section: Introductionmentioning
confidence: 99%
“…No se encuentra totalmente aclarado el papel de la proteína C-reactiva en la periodontitis, sin embargo algunos trabajos (11,16,23,24) intentan desvelar una posible relación entre la inflamación crónica, mediadores inflamatorios e imunológicos provenientes de la enfermedad periodontal con el aumento del riesgo de enfermedades cardiovasculares.…”
Section: Discussionunclassified
“…Basado en la publicación Asociación Americana del Corazón y del Centro para Controle de las Enfermedades en 2003, las concentraciones plasmáticas de PCR-US obtenidas por debajo de 0,1 mg/dL son consideradas de bajo riesgo de desarrollo de enfermedades cardiovasculares, mientras concentraciones variando entre 0,1-0,3 mg/dL son consideradas de mediano riesgo. Concentraciones mayores que 0,3 mg/dL se asocian con un mayor riesgo de desarrollo de enfermedades cardiovasculares siendo considerada la concentración de 0,3 mg/dL el punto de corte para definir individuos de alto riesgo cardiovascular (11). A la luz de los resultados obtenidos, la concentración promedio de PCR-US encontrada en el presente estudio para los pacientes con enfermedad periodontal fue de 0,36 mg/dL, mientras que en los individuos sin enfermedad periodontal esa concentra-ción presentó una media de 0,17 mg/dL.…”
Section: Tabla 4-estadística Descriptiva De La Concentración De Pcr-unclassified
See 1 more Smart Citation
“…Traditionally, the total number of WBC in peripheral blood has been used as a diagnostic measure to investigate whether a given individual suffers from an infection or inflammatory disease [11]. Studies have reported the relation between periodontal disease and inflammatory markers including CRP level [7][8][9][10][11][12][13][14][15][16][17] and WBC count [18,19]. Additionally, many clinical periodontal parameters were included, such as the number of missing teeth, clinical attachment level (CAL), periodontal probing depth (PD) and bleeding on probing (BOP), to determine the effect on systemic biomarkers, respectively.…”
Section: Introductionmentioning
confidence: 99%